The hypothalamus and periaqueductal gray are the sources of dopamine fibers in the paraventricular nucleus of the thalamus in the rat - Li, Sa; Shi, Yuxiu; Kirouac, Gilbert J. (Frontiers in Neuroanatomy, 2014)
The paraventricular nucleus of the thalamus (PVT) sends a very dense projection to the nucleus accumbens. This area of the striatum plays a key role in motivation and recent experimental evidence indicates that the PVT may have a similar function. It is well known that a dopaminergic projection from the ventral tegmental area (VTA) to the nucleus accumbens is a key regulator of motivation and reward-related behavior. Dopamine (DA) fibers have also been localized in the PVT but the source of these fibers in the rat has not been unequivocally identified. The present study was done to re-examine this question. Small iontophoretic injections of cholera toxin B (CTb) were made in the PVT to retrogradely label tyrosine hydroxylase (TH) neurons. Neurons that were double-labeled for TH/CTb were found scattered in DA cell groups of the hypothalamus (ventrorostral A10, A11, A13, A15 DA cell groups) and the midbrain (dorsocaudal A10 embedded in the periaqueductal gray). In contrast, double-labeled neurons were absent in the retrorubral field (A8), substantia nigra (A9) and VTA (A10) of the midbrain. We conclude that DA fibers in the PVT do not originate from VTA but from a heterogeneous population of DA neurons located in the hypothalamus and periaqueductal gray.